Medical Imaging 2013: Physics of Medical Imaging 2013
DOI: 10.1117/12.2007958
|View full text |Cite
|
Sign up to set email alerts
|

Iterative image reconstruction for sparse-view CT using normal-dose image induced total variation prior

Abstract: X-ray computed tomography (CT) iterative image reconstruction from sparse-view projection data has been an important research topic for radiation reduction in clinic. In this paper, to relieve the requirement of misalignment reduction operation of the prior image constrained compressed sensing (PICCS) approach introduced by Chen et al, we present an iterative image reconstruction approach for sparse-view CT using a normal-dose image induced total variation (ndiTV) prior. The associative objective function of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…However, orthogonal wavelets may lead to blocky artifacts in image reconstruction [ 14 17 ]. On the contrary, redundant wavelets, such as X-let [ 18 24 ] and others [ 25 31 ], can significantly improve the image quality [ 14 17 ]. Some of these transforms, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, orthogonal wavelets may lead to blocky artifacts in image reconstruction [ 14 17 ]. On the contrary, redundant wavelets, such as X-let [ 18 24 ] and others [ 25 31 ], can significantly improve the image quality [ 14 17 ]. Some of these transforms, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The study results using the patient CT data are shown in Figs. 7,8,9,10,11,12. In this study set, measurements from 1200 views over 360°are considered as a full sinogram, and measurements from 400 views over 360°are considered as an under-sampled sinogram. The detector had 896 bins for each view.…”
Section: Computer Simulationsmentioning
confidence: 99%
“…Many systematic studies lead to more efficient sampling criteria [4][5][6][7][8], where more complicated two-dimensional interpolations are discussed. According to compressed sensing theory, sparse-view tomography may still be possible if some image domain constraints are used to compensate for the missing data [9][10][11][12][13][14][15]. However, this paper focuses on analytic filtered backprojection (FBP) reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…More reconstruction methods based on NLM have been studied since then Refs. [11][12][13]. However, reconstruction methods using NLM often lead to over-smoothed images.…”
Section: Introductionmentioning
confidence: 97%
“…5 To solve this problem, many iterative methods have been studied for a long time. [6][7][8][9][10][11][12][13] Among them, total variation (TV) based methods [6][7][8][9] have reported overwhelming success in few-view CT reconstruction. The idea of TV is based on the fact that medical images could be sparsified by taking the gradient transform and the reconstruction could be optimized by solving a constrained minimization problem.…”
Section: Introductionmentioning
confidence: 99%